OP0120 Roles of B Cell Leukemia/Lymphoma 3 in The Development of T Follicular Helper Cells and the Pathogenesis of Rheumatoid Arthritis. (9th June 2015) - Meguro, K.; Suzuki, K.; Hosokawa, J.; Sanayama, Y.; Tanaka, S.; Furuta, S.; Ikeda, K.; Takatori, H.; Suto, A.; Ohara, O.; Nakajima, H.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease and proinflammatory cytokines such as TNFα and IL-6 play critical roles in the pathogenesis of RA. The blockade of IL-6 signaling by Tocilizumab (TCZ) has shown the clinical efficacy for patients with RA. To clarify the roles of IL-6 signaling in CD4 + T cells in the pathogenesis of RA, we previously compared gene expression profiles of CD4 + T cells by DNA microarray analysis before and after the treatment with TCZ in RA patients who exhibited good clinical responses to the treatment (1, 2), and identified that B cell leukemia/lymphoma 3 (Bcl3), an IκB family member, was down-regulated by TCZ therapy (1). However, the role of Bcl3 expressed in CD4 + T cells in the pathogenesis of RA remains unclear. Objectives: The objective of this study is to examine the role of Bcl3 expressed in CD4 + T cells in the pathogenesis of RA. Methods: We compared signal intensity of Bcl3 in CD4 + T cells between untreated RA patients and healthy controls by DNA microarray analysis. We examined the roles of IL-6-STAT3 signaling in Bcl3 induction. We also analyzed gene expression profiles of Bcl3-transduced CD4 + T cells by RNA-sequencing analysis. We examined the effect of enforced expression as well as gene silencing of Bcl3 on the development of T follicular helper (Tfh) cells. Finally, we examined a correlation between signal intensities of Bcl3 and Tfh cell-related genes in CD4 + T cells in untreated RA patients. Results: Bcl3 levels were significantly higher in RA patients than those in healthy controls. IL-6 induced Bcl3 expression in CD4 + T cells in a STAT3-dependent manner. Transcriptome analysis revealed that the expression of Bcl6, a master regulator of Tfh cell differentiation, was significantly upregulated by the enforced Bcl3 expression (Figure1 ). The enforced Bcl3 expression increased but the Bcl3 silencing decreased IL-21-producing Tfh-like cells. Bcl3 levels were positively correlated with those of Tfh cell-related genes such as CXCR5, ICOS, and ASCL2 in CD4 + T cells in RA patients. Conclusions: Bcl3 is involved in the development of Tfh cells and the pathogenesis of RA presumably by inducing IL-21 production. References: Saito Y, Kagami SI, Sanayama Y, Ikeda K, Suto A, Kashiwakuma D, et al. AT-rich interactive domain-containing protein 5a functions as a negative regulator of RORγt-induced Th17 cell differentiation. Arthritis Rheum. 2014;66(5):1185-94. Sanayama Y, Ikeda K, Saito Y, Kagami S, Yamagata M, Furuta S, et al. Prediction of therapeutic responses to tocilizumab in patients with rheumatoid arthritis: biomarkers identified by analysis of gene expression in peripheral blood mononuclear cells using genome-wide DNA microarray. Arthritis Rheum. 2014;66(6):1241-31. Disclosure of Interest: K. Meguro: None declared, K. Suzuki: None declared, J. Hosokawa: None declared, Y. Sanayama: None declared, S. Tanaka: None declared, S. Furuta: None declared, K. Ikeda: None declared, H. Takatori: None declared, A. Suto: None declared, O. Ohara: None declared, H. Nakajima Grant/research support from: Chugai Pharmaceutical Co., Ltd, Bristol-Myers Squibb, and Mitsubishi Tanabe Pharma Co.